Reliability-cost trade-offs for electricity industry planning with high variable renewable energy penetrations in emerging economies: A case study of Indonesia's Java-Bali grid. (15th July 2021) - Tanoto, Yusak; Haghdadi, Navid; Bruce, Anna; MacGill, Iain
Abstract: Electricity industries in emerging economies face particular challenges in delivering affordable, environmentally sustainable, and secure power given growing demand and limited financial resources. While supply reliability is often poor and emission reductions given lower priority, solar and wind are now amongst our cheapest supply options but highly variable. Our study seeks to demonstrate the potential value of trading-off reliability standards against higher renewables and lower industry costs in future generation planning. We use an open-source, evolutionary programming-based, capacity expansion planning tool, NEMO, to solve least cost generation mixes for Indonesia's Java-Bali grid in 2030. We explicitly test the cost and emission impacts of reliability targets of 0.005%–5% unserved energy (USE), modelled as both a hard optimization constraint and a penalty price on USE in the cost function. Our results highlight that lower reliability targets can increase solar and wind penetrations, reducing CO2 emissions while reducing industry costs. Both methods of incorporating reliability delivered similar outcomes but pricing USE had some advantages for optimization over hard constraint setting. While the impacts of lower reliability on consumers requires careful consideration, our study highlights the potential cost and emission implications of arguably unrealistic reliability targets in generation planning for emerging economies. Highlights: Future high renewables scenarios are simulated using open-source modelling. Cost and generation mix implications of different reliability targets are assessed. Reliability is expressed in optimization by fixing and pricing unserved energy (%USE). Both methods show a 5–10% increased renewables share for all scenarios at 5% USE. Cost reductions (/year) of around 13% are obtained across all scenarios at 5% USE.